Modified reinforced recycled aggregate, preparation method thereof and large-dosage road base
Patent Information
- Application Number
- CN202610940569.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-27
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]针对上述现有技术的不足,本发明所要解决的技术问题是:如何提供一种改性强化再生骨料及其制备方法和大掺量道路基层,解决现有改性再生骨料仍存在孔隙率高、吸水率大及深微裂纹难以修复的固有缺陷,以及传统细菌单向矿化膜脆性大、易脱落、矿化深度有限和碳化效率低,导致再生骨料在道路工程中掺量低(通常<30%)的局限问题
1、本发明的制备方法,采用真空负压工艺打破再生骨料微裂纹的毛细管气阻,将复合矿化液强制吸入骨料内部3~5mm深处,利用土曲霉菌丝的三维生长特性在再生骨料内部构建“菌丝-碳酸钙”交织网络。在此基础上,创新性地引入高浓度短脉冲渗透和扩散反应的碳硫化工艺,该工艺成功将高浓度与低总硫量解耦,以菌丝网络为生物模板,在骨料内外同步生成“菌丝-碳酸钙-钙矾石”三元复合矿化层,该工艺实现了从骨料内部3~5mm微裂纹到骨料表面的由内而外、从微观到宏观的全方位靶向缺陷修复,不仅显著提升了骨料自身强度与界面相容性,且SO3的存在可加速碱性组分的溶出速率,显著提升CO2碳化反应效率,整体碳化时间从传统单一CO2碳化的12h以上缩短至2~3h,反应效率提高75%以上。同时,从根本上解决了高浓度SO3瞬时反应导致的表面封孔、膨胀开裂与酸溶破坏难题,实现骨料缺陷由内而外的全方位靶向修复。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of road engineering and solid waste resource utilization technology, specifically to a modified and reinforced recycled aggregate, its preparation method, and a road base course with high admixture content. Background Technology
[0002] With the acceleration of urbanization in my country, approximately 3.5 billion tons of construction waste are generated annually, of which waste concrete accounts for over 60%. Processing this waste into recycled aggregate to replace natural aggregate for road base courses is a core approach to solving the problem of construction waste surrounding cities and alleviating the shortage of natural sand and gravel resources. However, recycled aggregate has inherent defects such as high porosity (15%~30%), high water absorption (6%~15%), high crushing value (>30%), and poor interfacial bonding performance due to its surface being covered with a large amount of old cement mortar. As a result, its engineering admixture is generally less than 30%, making large-scale resource utilization impossible.
[0003] To improve the performance of recycled aggregates, existing technologies mainly employ physical, chemical, biomineralization, and carbonization strengthening methods. For example, invention patent CN118084377A discloses microbial mineralization of recycled coarse aggregates and solidified concrete with fully recycled aggregates, its preparation method, and application. This method involves directly spraying Bacillus pasteurellium solution onto the surface of recycled coarse aggregates and combining it with a mineralizing nutrient solution for curing. Bacterial-induced calcium carbonate precipitation fills the pores, but the mineralization depth is limited (<2mm), and the resulting bacterial mineralization film is brittle with no support between minerals, making it prone to detachment during mixing and service. Invention patent CN120192108A discloses a microbial mineralization-modified recycled aggregate, its preparation method, and application, proposing the use of microorganisms with both nitrification and denitrification capabilities (such as Paracoccus azotocinus) mixed with urealytic bacteria to mineralize recycled aggregates. However, the mineralization product remains a single calcium carbonate (calcite). The single calcium carbonate crystal structure is highly susceptible to secondary dissolution under acid rain or chloride erosion, and cannot penetrate and fill the 3-5 mm deep microcrack core area inside recycled aggregate. For example, invention patent CN117303774A discloses an interface-reinforced recycled aggregate, its preparation method, and recycled aggregate concrete. This method involves treating the recycled aggregate with Trichoderma longicornis and then immersing it in a reinforcing liquid composed of copovidone and hydroxyethyl cellulose. This method mainly relies on chemical polymers forming a film on the aggregate surface to reduce water absorption and enhance the interface. However, organic chemical polymers exhibit poor long-term weather resistance and durability in complex road base environments, and the process is complex. Furthermore, while carbonation technology using only carbon dioxide (CO2) can react with alkaline substances on the aggregate surface to generate calcium carbonate, this reaction only occurs on the surface and cannot penetrate into the internal pores. Additionally, the carbonation time is long (over 12 hours), resulting in low efficiency.
[0004] Therefore, how to achieve comprehensive repair of internal and external defects in recycled aggregates through process innovation, and thus improve the application of recycled aggregates in road base courses, remains a technical challenge that urgently needs to be solved in the field of solid waste-based road materials. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is: how to provide a modified and reinforced recycled aggregate and its preparation method and a road base course with large dosage, so as to solve the inherent defects of existing modified recycled aggregates, such as high porosity, high water absorption and difficulty in repairing deep microcracks, as well as the limitations of traditional bacterial unidirectional mineralization film, which is brittle, easy to fall off, limited mineralization depth and low carbonization efficiency, resulting in low dosage of recycled aggregate in road engineering (usually <30%).
[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: a method for preparing modified and reinforced recycled aggregate, comprising the following steps: S1: Multi-stage crushing and screening of construction waste to obtain continuously graded recycled aggregate; multi-stage crushing and shaping processes are used to remove loose mortar from the surface of the aggregate, optimize particle morphology, and reduce the content of needle-shaped and flaky particles.
[0007] S2: Place the recycled aggregate treated in step S1 into a vacuum impregnation tank, then remove the air from the pores inside the aggregate under vacuum negative pressure, and then inject Aspergillus terrestris composite mineralization liquid until the recycled aggregate is completely submerged. After impregnation and coating treatment under normal pressure, take it out, drain it, and carry out mineralization curing treatment to obtain pre-mineralized recycled aggregate; the mineralization depth can reach 3~5mm inside the aggregate, effectively filling all microcracks and pores; forming a "mycelium-calcium carbonate" interwoven network structure, the mineralization film is extremely tough and has no brittle fracture.
[0008] S3: Place the pre-mineralized recycled aggregate obtained in step S2 in a sealed carbonization box, preferably with a spreading thickness ≤5cm. Heat to 50~60℃, evacuate to an absolute pressure of 10~50kPa, and maintain for 5~30min to completely remove residual air from the aggregate pores, reducing the surface moisture content of the aggregate to below 1% to prevent high-concentration SO3 from reacting instantaneously with water and sealing the pores. Maintain a negative pressure state, introduce a preheated mixed gas containing CO2 and SO3, and rapidly increase the pressure to atmospheric pressure within 30~120s. Driven by the pressure difference, high-concentration SO3 and CO2 simultaneously penetrate into the microcracks 3~5mm deep inside the aggregate, uniformly adsorbed on the pore walls and the surface of Aspergillus terreus hyphae, completing the gas-phase high-concentration pulsed infiltration. Stop the introduction of SO3, and carry out a diffusion reaction in a CO2 atmosphere, allowing the SO3 adsorbed in the pores to gradually react with the alkaline components, generating a composite mineralized layer interwoven with ettringite and calcium carbonate. After the reaction is completed, the modified and reinforced recycled aggregate is obtained. In this way, by introducing a high-concentration pulsed infiltration and diffusion reaction carbonization process, using fungal hyphae as a natural biological template, CO2 reacts with the alkaline hydration components on the aggregate surface and within the pores to generate calcium carbonate crystals, while SO3 reacts with the calcium-aluminum phase components to generate needle-like ettringite crystals. Both types of products grow directionally along the three-dimensional network of hyphae and intertwine with each other, tightly combining with the calcium carbonate layer generated by the previous biomineralization. Together, they form a dense "hyphae-calcium carbonate-ettringite" ternary composite inorganic mineralization layer in the pores and on the surface of the aggregate. This process achieves comprehensive targeted defect repair from the inside out and from the microscopic to the macroscopic, from 3-5 mm microcracks inside the aggregate to the aggregate surface. It not only significantly improves the strength and interfacial compatibility of the aggregate itself, but the presence of SO3 can accelerate the dissolution rate of alkaline components, significantly improving the efficiency of CO2 carbonization reaction. The overall carbonization time is shortened from more than 12 hours in traditional single CO2 carbonization to 2-3 hours, and the reaction efficiency is increased by more than 75%.
[0009] Preferably, the construction waste is at least one of waste concrete blocks, brick slag, and waste stone slag; in the continuously graded recycled aggregate, the mass fraction of particles with a diameter of 20-31.5 mm is 30%-40%, the mass fraction of particles with a diameter of 10-20 mm is 30%-40%, the mass fraction of particles with a diameter of 2.36-10 mm is 20%-30%, and the sum of the mass fractions of each particle size component is 100%. Precise sieving forms a continuous gradation, constructing a dense skeleton structure. This not only provides a foundation for the high mechanical properties of the subsequent road base layer but also lays a good spatial physical condition for the effective penetration growth and network mineralization of fungal hyphae.
[0010] Preferably, the Aspergillus terrestris composite mineralization solution comprises Aspergillus terrestris mycelium, calcium chloride, and sodium alginate. The molar concentration of calcium chloride is 0.5-0.6 mol / L, the mass concentration of sodium alginate is 1-3 g / L, and the mass concentration of Aspergillus terrestris mycelium is 5-8 g / L. In this way, the mycelium can penetrate 3-5 mm into the microcracks within the aggregate, effectively filling the microcracks and pores to form a continuous three-dimensional network structure, serving as a natural supporting framework for the mineralization products. Calcium chloride acts as a calcium source, providing raw materials for the formation of calcium carbonate. Sodium alginate, as a biological carrier, possesses excellent film-forming and adhesive properties, enhancing the adhesion of the mycelium within the aggregate pores and prolonging the mycelial residence time. The synergistic effect of these three components ensures the formation of a highly resilient biomineral layer, preventing brittle fracture and thus achieving deep and comprehensive repair of the aggregate.
[0011] Preferably, the Aspergillus terreus strain is Aspergillus terreus CGMCC 3.10144. This strain was isolated from saline-alkali soil and has extremely strong alkali resistance, growing stably within a wide pH range of 2.5 to 12.5, and can adapt to the strongly alkaline surface of recycled aggregates (pH 11.5 to 12.5). It also possesses dual mineralization pathways of urease and carbonic anhydrase, greatly improving mineralization efficiency. The secreted extracellular polysaccharides further endow the mineralized film with extremely strong toughness, allowing it to withstand the mechanical damage of subsequent stirring and rolling.
[0012] Preferably, the vacuum degree of the vacuum negative pressure is -0.09 to -0.095 MPa; the impregnation and coating time is 0.5 to 1.0 h; the temperature during the mineralization curing process is 28 to 32°C, the relative humidity is 85% to 95%, and the time is 16 to 20 h. In this way, the high vacuum degree forcibly removes the air "air resistance" within the capillaries of the recycled aggregate, and the huge pressure difference formed when restoring normal pressure instantly forces the mineralizing liquid into the internal microcracks, ensuring the "deep targeting" of the mineralization treatment. At the same time, precise temperature and humidity control compresses the efficient mineralization cycle of the fungus to within 16 to 20 h, greatly improving the processing efficiency.
[0013] Preferably, in step S3, the total SO3 injection rate in the high-concentration pulsed infiltration is 1.2% to 1.8% of the dry mass of the aggregate, resulting in a final aggregate bound SO3 content of 0.9% to 1.3%; the diffusion reaction is carried out for 1.5 to 2.0 hours at a CO2 volume concentration of 20% to 25%, a relative humidity of 30% to 55%, and a temperature of 50 to 60°C; the SO3 volume concentration in the mixed gas is 8% to 12%, and the CO2 volume concentration is 20% to 30%; the preheating temperature is 50 to 60°C.
[0014] In this way, within an extremely short time of 30-120 seconds, a gas containing a high concentration of SO3 (8%-12%) is instantly forced into the microcracks inside the aggregate using a pressure difference and adsorbed onto the pore walls. This operation successfully decouples the high permeability concentration from the low total sulfur content, keeping the total sulfur load within an absolutely safe volume stability threshold, avoiding the risk of delayed expansion cracking in the later stages, and fundamentally preventing cracking of the mineralized layer and surface pore sealing. At the same time, the presence of SO3 significantly accelerates the dissolution of alkaline components in the aggregate, reduces the activation energy of the CO2 carbonization reaction, and drastically shortens the total carbonization cycle from over 12 hours to about 2 hours.
[0015] Preferably, the diffusion reaction employs a gradient humidification method to control relative humidity: in the first stage, the relative humidity is 30%–40% for the first 20–30 minutes; in the second stage, the relative humidity is gradually increased to 45%–55%. Firstly, under low humidity conditions, water is prevented from prematurely sealing the micropores, thus ensuring that SO3 gas trapped within the pores can slowly and controllably diffuse into the deeper pores. Then, increasing the humidity appropriately ensures the hydration conditions for the nucleation and crystal growth of acicular ettringite, generating acicular ettringite crystals with micro-expansion characteristics. The ettringite grows directionally along the hyphae like wedges and intersects between calcium carbonate particles, ensuring that ettringite and calcium carbonate are densely and uniformly directionally generated within the pores.
[0016] Another objective of this invention is to provide a modified and reinforced recycled aggregate prepared by the above method. The modified recycled aggregate, through this process, has internal pores tightly filled with needle-like ettringite and calcium carbonate (microcrack filling rate ≥90%), forming a deep, sealed layer with extremely low porosity. This effectively blocks moisture intrusion. The modified recycled aggregate has a crushing index ≤19%, a moisture content ≤5%, and a water absorption rate ≤3.0%. The water absorption rate meets the requirements of Class I recycled coarse aggregate in GB / T 25177-2010, and the crushing index meets the requirements of Class II recycled coarse aggregate. Simultaneously, the outer filamentous mycelial network provides strong organic anchoring points, thoroughly improving the tendency of the inorganic modified layer to easily peel off brittlely, achieving a balance between high strength and high durability.
[0017] Another objective of this invention is to provide a road base course with a high proportion of recycled aggregate, comprising the following dry aggregate components in parts by weight: 70-90 parts of the aforementioned modified and reinforced recycled aggregate, 3-5 parts of cement, 5-7 parts of slag powder, and 0-20 parts of natural fine aggregate. The significantly enhanced surface activity and inherent strength of the modified recycled aggregate allow its dry aggregate content to jump to 70%-90%. Only a very small amount of cement and slag powder are needed for activation in the system, along with a small amount of natural fine aggregate to optimize the gradation, to construct an extremely stable road load-bearing layer.
[0018] Another objective of this invention is to provide a method for preparing a road base course with a high content of recycled aggregate, comprising the following steps: weighing the above-mentioned modified and reinforced recycled aggregate, cement, slag powder and natural fine aggregate according to the proportion, and dry mixing for 2-3 minutes to mix evenly; then adding mixing water (calculated according to the optimum moisture content determined by the heavy compaction test specified in the highway geotechnical test procedure), and wet mixing for 3-5 minutes to obtain the base course mixture; spreading and compacting the mixture to a compaction degree ≥97%, and then covering and watering for curing for at least 7 days to obtain the road base course with a high content of recycled aggregate.
[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The preparation method of this invention employs a vacuum negative pressure process to break the capillary air resistance of microcracks in recycled aggregates, forcibly drawing the composite mineralizing liquid into the aggregate interior to a depth of 3-5 mm. Utilizing the three-dimensional growth characteristics of Aspergillus terreus hyphae, a "hyphae-calcium carbonate" interwoven network is constructed within the recycled aggregate. Based on this, a novel carbon sulfidation process involving high-concentration short-pulse penetration and diffusion reactions is introduced. This process successfully decouples high concentration from low total sulfur content, using the hyphal network as a biological template to simultaneously generate a "hyphae-calcium carbonate-ettringite" ternary composite mineralization layer inside and outside the aggregate. This process achieves comprehensive targeted defect repair from the inside out, from the microscopic to the macroscopic, from the 3-5 mm microcracks inside the aggregate to the aggregate surface. This not only significantly improves the aggregate's own strength and interfacial compatibility, but the presence of SO3 accelerates the dissolution rate of alkaline components, significantly improving the CO2 carbonization reaction efficiency. The overall carbonization time is shortened from over 12 hours in traditional single CO2 carbonization to 2-3 hours, with a reaction efficiency increase of over 75%. At the same time, it fundamentally solves the problems of surface sealing, expansion cracking and acid dissolution damage caused by the instantaneous reaction of high concentration SO3, and realizes all-round targeted repair of aggregate defects from the inside out.
[0020] 2. The modified and reinforced recycled aggregate prepared by this invention possesses extremely high intrinsic strength and excellent interfacial compatibility. On one hand, the needle-like ettringite and calcium carbonate, uniformly generated at a depth of 3-5 mm through pulse penetration, are tightly interwoven, with a microcrack filling rate ≥90%, forming a deep, sealed layer with extremely low porosity. This effectively blocks the path of water intrusion, endowing the aggregate with excellent physical properties such as high strength (crushing value ≤19%) and ultra-low water absorption (≤3.0%). On the other hand, the unique filamentous structure of Aspergillus terreus provides a natural three-dimensional support framework for the deposition of inorganic minerals. Combined with its secreted extracellular polysaccharides, ettringite crystals grow directionally along the hyphae and are firmly anchored, significantly enhancing the interfacial adhesion between the mineralized layer and the matrix. This completely solves the industry problem of the traditional single biomineralized layer being brittle and easily peeled off.
[0021] 3. When modified and reinforced recycled aggregate is applied to road base courses, the mass content can jump to 70%~90%, achieving a large-scale utilization of construction solid waste. The prepared high-volume recycled aggregate road base course requires only a very small amount of cement and slag powder for activation, enabling the compacted roadbed to exhibit excellent compressive strength and anti-interlocking ability. Its 7-day unconfined compressive strength is ≥4.0MPa, 28-day unconfined compressive strength is ≥5.5MPa, and 7-day water stability coefficient is ≥94%, fully meeting the technical requirements of Class I highways. This solution not only significantly reduces the use of high-energy-consuming cement and the amount of natural sand and gravel mined, reducing engineering costs by more than 30%, but also achieves large-scale, high-value-added resource utilization of construction waste. Detailed Implementation
[0022] The present invention will be further described in detail below with reference to embodiments, but the scope of protection of the present invention is not limited thereto. Unless otherwise specified, the experimental methods in the following embodiments are conventional methods; and unless otherwise specified, the materials used are commercially available.
[0023] The Aspergillus terreus used in this invention was purchased from the China General Microbiological Culture Collection Center, strain number CGMCC3.10144.
[0024] Example 1: A method for preparing a road base course with high-dosage modified and reinforced recycled aggregate, the specific steps of which are as follows: (1) Pretreatment of recycled aggregate: Waste concrete blocks are fed into a jaw crusher for primary coarse crushing, then into a cone crusher for secondary medium crushing, and finally into an impact crusher for tertiary shaping crushing to remove sharp edges and weak mortar layers from the aggregate surface. The crushed material is then screened by a vibrating screen to prepare continuously graded aggregate. The mass fraction of each particle size range is as follows: 20~31.5 mm 35%, 10~20 mm 35%, and 2.36~10 mm 30%. Simultaneously, the content of needle-like and flaky particles must be strictly controlled to ≤15%, and the mud content ≤1.0%.
[0025] (2) Activation and culture of strains: Strain activation: The freeze-dried Aspergillus terreus CGMCC 3.10144 was inoculated onto potato dextrose agar (PDA) slant medium and activated in a constant temperature incubator at 28°C for 72 h.
[0026] Seed culture: Three colonies with a diameter of 5 mm were picked and inoculated into seed culture medium (potato extract 200 g / L, glucose 20 g / L, urea 10 g / L, potassium dihydrogen phosphate 1 g / L, magnesium sulfate 0.5 g / L, pH 9.0), and cultured with shaking at 28℃ and 120 rpm for 36 h to obtain seed culture.
[0027] Fermentation broth culture: The seed culture was inoculated into the fermentation medium (corn steep liquor 25 g / L, urea 20 g / L, glucose 5 g / L, potassium dihydrogen phosphate 1 g / L, magnesium sulfate 0.5 g / L, pH 9.0) at a 10% inoculation rate and cultured with shaking at 28℃ and 120 rpm for 48 h to obtain a fermentation broth with a mycelial concentration of 6 g / L (wet weight).
[0028] (3) Preparation of composite mineralizing solution: Calcium chloride and sodium alginate were added to the above fermentation broth and stirred continuously until completely dissolved. The molar concentration of calcium chloride was controlled to reach 0.5 mol / L and the mass concentration of sodium alginate was controlled to reach 3 g / L to obtain a composite mineralization solution.
[0029] (4) Biological premineralization treatment: Continuously graded recycled aggregate is loaded into a vacuum impregnation tank, sealed, and evacuated to -0.09 to -0.095 MPa for 10 to 15 minutes to completely remove air from the pores inside the aggregate. While maintaining the vacuum, a composite mineralizing solution is injected into the tank until the recycled aggregate is completely submerged. The vacuum is then released, and the tank is allowed to stand for 1 hour to coat the aggregate. After the coating is completed, the recycled aggregate is removed and drained until there is no dripping water on the surface. It is then transferred to a constant temperature and humidity curing chamber at 28 to 32°C and 85% to 95% relative humidity for 16 hours to obtain pre-mineralized recycled aggregate.
[0030] (5) Carbon sulfidation treatment: The pre-mineralized recycled aggregate is evenly spread on the multi-layer material trays of the sealed carbonization box, with a spreading thickness of ≤5cm. After sealing, the temperature inside the box is raised to 50~60℃, and a vacuum is first drawn to an absolute pressure of 20~30kPa and maintained for 10~15min to completely remove the residual air in the aggregate pores. At the same time, the surface moisture content of the aggregate is reduced to a dry state of less than 1% to avoid the instantaneous reaction of high concentration SO3 with water on the surface and sealing of the pores.
[0031] Maintaining a negative pressure state, a mixture of CO2 and SO3 gas preheated to 50~60℃ is introduced, controlling the volume concentration of SO3 in the mixture to be 12% and the volume concentration of CO2 to be 25%. Then, the pressure is rapidly increased to atmospheric pressure within 60 seconds. Driven by the pressure difference, the high-concentration SO3 and CO2 simultaneously penetrate into the microcracks 3~5mm deep inside the aggregate, and are uniformly adsorbed on the pore walls and the surface of Aspergillus terreus hyphae, completing the deep gas phase penetration.
[0032] Stop the SO3 supply and maintain the CO2 volume concentration in the chamber at 20%~25%. Initiate the diffusion reaction using a gradient humidification strategy: In the first stage, maintain a relative humidity of 30% for the first 30 minutes to ensure that SO3 continues to diffuse deeper into the pores; in the second stage, gradually increase the relative humidity to 45% and maintain a constant temperature for 1.5~2.0 hours. After the reaction is complete, stop the aeration, slowly cool to room temperature, and remove the aggregate to air dry naturally until the moisture content is ≤5%, thus obtaining the modified and reinforced recycled aggregate.
[0033] (6) Preparation of road base mixture: Weigh the following components according to the dry basis mass ratio: reinforced recycled aggregate: 90 parts, PO 42.5 ordinary Portland cement: 5 parts, S95 grade slag powder: 5 parts. Pour the above dry materials into a forced mixer and dry mix for 2-3 minutes until uniform. Then add the mixing water calculated according to the optimum moisture content determined by the heavy compaction test specified in the highway geotechnical test procedure, and wet mix for 3-5 minutes to obtain a uniform base course mixture, and control the initial flowability ≥160mm.
[0034] (7) Paving and compaction: The mixed material is spread out and compacted with a heavy roller to a compaction degree of ≥97%. After compaction, the surface is covered with geotextile and watered for curing. The curing period is 7 days, which yields a road base course with a high content of recycled aggregate.
[0035] Example 2: A method for preparing a road base course with high-dosage modified and reinforced recycled aggregate, the specific steps of which are as follows: (1) Pretreatment of recycled aggregate: Waste concrete blocks are fed into a jaw crusher for primary coarse crushing, then into a cone crusher for secondary medium crushing, and finally into an impact crusher for tertiary shaping crushing to remove sharp edges and weak mortar layers from the aggregate surface. The crushed material is then screened by a vibrating screen to prepare continuously graded aggregate. The mass fraction of each particle size range is as follows: 20~31.5 mm 40%, 10~20 mm 40%, and 2.36~10 mm 20%. Simultaneously, the content of needle-like and flaky particles must be strictly controlled to ≤15%, and the mud content ≤1.0%.
[0036] (2) Activation and culture of strains: Strain activation: The freeze-dried Aspergillus terreus CGMCC 3.10144 was inoculated onto potato dextrose agar (PDA) slant medium and activated in a constant temperature incubator at 28°C for 72 h.
[0037] Seed culture: Three colonies with a diameter of 5 mm were picked and inoculated into seed culture medium (potato extract 200 g / L, glucose 20 g / L, urea 10 g / L, potassium dihydrogen phosphate 1 g / L, magnesium sulfate 0.5 g / L, pH 9.0), and cultured with shaking at 28℃ and 120 rpm for 36 h to obtain seed culture.
[0038] Fermentation broth culture: The seed culture was inoculated into the fermentation medium (corn steep liquor 25 g / L, urea 20 g / L, glucose 5 g / L, potassium dihydrogen phosphate 1 g / L, magnesium sulfate 0.5 g / L, pH 9.0) at a 10% inoculation rate and cultured with shaking at 28℃ and 120 rpm for 48 h to obtain a fermentation broth with a mycelial concentration of 8 g / L (wet weight).
[0039] (3) Preparation of composite mineralizing solution: Calcium chloride and sodium alginate were added to the above fermentation broth and stirred continuously until completely dissolved. The molar concentration of calcium chloride was controlled to reach 0.6 mol / L and the mass concentration of sodium alginate was controlled to reach 1 g / L to obtain a composite mineralization solution.
[0040] (4) Biological premineralization treatment: Continuously graded recycled aggregate is loaded into a vacuum impregnation tank, sealed, and evacuated to -0.09 to -0.095 MPa for 10 to 15 minutes to completely remove air from the pores inside the aggregate. While maintaining the vacuum, a composite mineralizing solution is injected into the tank until the recycled aggregate is completely submerged. The vacuum is then released, and the tank is allowed to stand for 0.5 hours for impregnation and coating. After impregnation and coating, the recycled aggregate is removed and drained until there is no dripping water on the surface. It is then transferred to a constant temperature and humidity curing chamber at 28 to 32°C and 85% to 95% relative humidity for 20 hours for mineralization curing to obtain pre-mineralized recycled aggregate.
[0041] (5) Carbon sulfidation treatment: The pre-mineralized recycled aggregate is evenly spread on the multi-layer material trays of the sealed carbonization box, with a spreading thickness of ≤5cm. After sealing, the temperature inside the box is raised to 50~60℃, and a vacuum is first drawn to an absolute pressure of 20~30kPa and maintained for 10~15min to completely remove the residual air in the aggregate pores. At the same time, the surface moisture content of the aggregate is reduced to a dry state of less than 1% to avoid the instantaneous reaction of high concentration SO3 with water on the surface and sealing of the pores.
[0042] Maintaining a negative pressure state, a mixture of CO2 and SO3 gas preheated to 50-60℃ is introduced, controlling the SO3 volume concentration in the mixture to be 8% and the CO2 volume concentration to be 30%. Then, the pressure is rapidly increased to atmospheric pressure within 60 seconds. Driven by the pressure difference, the high-concentration SO3 and CO2 simultaneously penetrate into the microcracks 3-5mm deep inside the aggregate, and are uniformly adsorbed on the pore walls and the surface of Aspergillus terrestris hyphae, completing the deep gas phase penetration.
[0043] Stop the SO3 supply and maintain the CO2 volume concentration in the chamber at 20%~25%. Initiate the diffusion reaction using a gradient humidification strategy: In the first stage, maintain a relative humidity of 40% for the first 20 minutes to ensure that SO3 continues to diffuse deeper into the pores; in the second stage, gradually increase the relative humidity to 55% and maintain a constant temperature for 1.5~2.0 hours. After the reaction is complete, stop the aeration, slowly cool to room temperature, and remove the aggregate to air dry naturally until the moisture content is ≤5%, thus obtaining the modified reinforced recycled aggregate.
[0044] (6) Preparation of road base mixture: Weigh the following components according to the dry basis mass ratio: reinforced recycled aggregate: 70 parts, PO 42.5 ordinary Portland cement: 4 parts, S95 grade slag powder: 6 parts, and natural fine aggregate: 20 parts. Pour the above dry materials into a forced mixer and dry mix for 2-3 minutes until uniform. Then add the mixing water calculated according to the optimum moisture content determined by the heavy compaction test specified in the Highway Geotechnical Test Procedure, and wet mix for 3-5 minutes to obtain a uniform base course mixture, controlling the initial flowability ≥160mm.
[0045] (7) Paving and compaction: The mixed material is spread out and compacted with a heavy roller to a compaction degree of ≥97%. After compaction, the surface is covered with geotextile and watered for curing. The curing period is 10 days, which yields a road base course with a high content of recycled aggregate.
[0046] Comparative Example 1: In this comparative example, the recycled aggregate was not subjected to bio-premineralization treatment and carbon sulfidation treatment, and the other steps were the same as in Example 1.
[0047] Comparative Example 2: No carbon sulfidation treatment was performed in this comparative example; the other steps were the same as in Example 1.
[0048] Comparative Example 3: No bio-premineralization was performed in this comparative example; the other steps were the same as in Example 1.
[0049] Comparative Example 4: In this comparative example, the same mass concentration of Bacillus siberianis bacterial solution was used to replace the Aspergillus terreus fermentation broth in the preparation of the mineralization solution. Other steps and mineralization maintenance conditions were the same as in Example 1.
[0050] II. Performance Verification 1. The modified recycled aggregates prepared in Examples 1-2 and Comparative Examples 1-4 were placed in a standard laboratory environment at a temperature of 20±2℃ and a relative humidity of 50±5% for 24 hours until they stabilized. Then, physical and mechanical properties, water absorption and film-forming durability were tested according to the methods specified in the national standard. The results are shown in Table 1.
[0051] Among them, water absorption rate: tested according to GB / T 14685-2011 "Construction Gravel and Crushed Stone", with a sample mass of 2000g and a soaking time of 24h; crushing value: tested according to GB / T 14685-2011 "Construction Gravel and Crushed Stone", using standard samples with a particle size of 10~20mm, a loading rate of 1kN / s, and a total load of 400kN; mineralization film retention rate: tested using the forced stirring method, 10kg of modified recycled aggregate was placed in a 50L forced mixer and stirred at a speed of 30r / min for 5min, and the mass change of aggregate before and after stirring was tested. The calculation formula is: mineralization film retention rate = (1 - mass loss rate after stirring) × 100%. Comparative Example 1 (unreinforced) had no mineralization film, so this index was not tested.
[0052] Table 1 As can be seen from Table 1, the water absorption rate of Examples 1 to 2 is ≤3.0%, which meets the water absorption rate requirements of Class I aggregates in GB / T 25177-2010 "Recycled Coarse Aggregate for Concrete"; the crushing value is ≤19%, which meets the crushing index requirements of Class II aggregates, and is fully consistent with the "internal and external synergistic all-round repair" goal of the process design. The water absorption rates of Aspergillus terreus bio-premineralization (Comparative Example 2) and pulsed carbon sulfidation (Comparative Example 3) alone were 5.3% and 5.7%, respectively, with crushing values in the range of 23% to 26%. However, the water absorption rate of the combined example decreased to 2.7% to 2.8%, and the crushing value decreased to 18% to 19%, showing a significant "1+1>2" synergistic effect: the mycelial network of bio-premineralization penetrates 3 to 5 mm into the aggregate, providing a growth template for carbon sulfidation products and solving the bottleneck that carbon sulfidation alone can only repair the surface layer of 1 to 2 mm; the ettringite and calcium carbonate generated by carbon sulfidation fill the gaps in the mycelial network, further densifying the mineralized structure and making up for the high porosity of bio-mineralization alone. When only pulsed carbon sulfidation is performed without bio-premineralization (Comparative Example 3), the performance is weaker than that of single biomineralization, and the mineralization film retention rate is only 74.3%. The core reason is that without mycelial template guidance, the gas phase reaction products can only be deposited on the surface of the aggregate and in shallow pores, and cannot repair internal microcracks, resulting in limited overall strengthening depth. The pure inorganic calcium carbonate-ettringite mineralization layer has no organic binder phase and is brittle, making it easy to peel off in sheets during forced stirring. Therefore, the retention rate is significantly lower than that of the system containing mycelial skeleton. Differences between bacterial and fungal systems (comparison of Example 4 and Example 1): The Siberian Bacillus system, when used with the same pulsed carbon sulfurization process, performed significantly worse than the Aspergillus terreus system, and the mineralization film retention rate was about 9 percentage points lower. The reasons are as follows: Bacillus is a single-celled organism and cannot form a three-dimensional hyphal network. The mineralization is mainly concentrated on the surface of the aggregate and cannot penetrate into the 3-5 mm microcracks, resulting in insufficient repair of internal defects. The calcium carbonate crystals induced by bacteria lack a flexible skeleton connection, making the mineralization film brittle and prone to falling off after stirring. This results in insufficient resistance to wear and erosion during long-term service.
[0053] 2. The road base mixtures prepared in Examples 1-2 and Comparative Examples 1-4 were molded into φ150mm×150mm cylindrical specimens according to the method specified in JTG 3441-2024 "Test Procedure for Inorganic Binder Stabilized Materials for Highway Engineering". Six parallel specimens were prepared for each group. After curing in a standard curing room at 20±2℃ and relative humidity ≥95% to the specified age, strength and durability tests were conducted. All tests were carried out in a standard laboratory environment at 20±2℃. The results were taken as the arithmetic mean of the six parallel specimens (coefficient of variation ≤15%). The test results are shown in Table 2.
[0054] Among them, the 7d / 28d unconfined compressive strength was tested according to JTG 3441-2024 T0805 "Test Method for Unconfined Compressive Strength of Inorganic Binder Stabilized Materials", with a loading rate of 1mm / min until the specimen failed. The maximum load was recorded and the compressive strength was calculated. The 7d water stability coefficient was tested according to JTG 3441-2024 T0843 "Test Method for Water Stability of Inorganic Binder Stabilized Materials". After the specimen was cured for 6 days under standard conditions, it was immersed in a water bath at a temperature of 20±2℃ for 24 hours, with the water level 2.5cm above the top surface of the specimen. After removing the specimen and drying the surface moisture, the compressive strength after 7 days of immersion was tested. The formula for calculating the water stability coefficient is: Water stability coefficient = (7-day immersion compressive strength / 7-day standard curing compressive strength × 100%).
[0055] Table 2 As shown in Table 2, the 7-day strength of Examples 1-2 all exceeded 4.0 MPa, meeting the strength requirements (3.0-5.0 MPa) for cement-stabilized base courses of highways and first-class roads. Example 2 was slightly superior to Example 1, partly because it had higher mycelial and calcium source concentrations, resulting in better aggregate performance; and partly because the 20% natural fine aggregate optimized the mixture gradation, filled the skeleton voids, and improved the overall density, offsetting the effect of the slightly lower cement content. The 7-day strengths of Comparative Example 2 (biological premineralization only) and Comparative Example 3 (carbon sulfidation only) were 3.2 MPa and 2.9 MPa, respectively, with an average of 3.05 MPa. Example 1, however, reached 4.0 MPa, an increase of over 30%, verifying the synergistic strengthening effect of "internal filling of the mycelial skeleton + surface densification by carbon sulfidation," rather than a simple superposition of the two processes. The 7-day and 28-day strengths of Comparative Example 4 were lower than those of Example 1. The core reason is that Bacillus is a single-celled organism and cannot form a three-dimensional hyphal network. The mineralization repair depth is insufficient, the microcracks inside the aggregate are not effectively filled, and the overall mechanical properties are weaker than those of the Aspergillus terreus system.
[0056] The water stability coefficient directly reflects the water resistance of the base layer and is negatively correlated with the aggregate water absorption rate and interfacial bonding performance. The example demonstrates optimal water stability: a water stability coefficient exceeding 94%, significantly higher than the industry average (typically 75%~85% for ordinary recycled aggregate base layers). There are two main reasons for this: first, the internal pores of the aggregate are filled with mycelium-mineralized products, reducing the water absorption rate from 11.2% to below 3%, preventing the aggregate from softening after immersion in water; second, the surface ternary composite mineralization layer has good compatibility with the cement paste, and the dense interfacial transition zone blocks the path of water penetration along the interface, avoiding strength loss due to interfacial peeling. Comparative Example 3 has a water stability coefficient of only 84.3%, lower than the single biological premineralization system. This is partly due to the weak interfacial bonding between the pure inorganic carbonization layer and the cement paste, making it prone to interfacial cracking after immersion in water; and partly due to the shallow depth of the single carbon sulfide repair, leaving numerous interconnected pores within the aggregate, allowing water to easily penetrate and soften the aggregate interior. Comparative Example 4 showed a better water stability coefficient than the two individual comparative examples, but weaker than the fungal system. Although bacterial mineralization can reduce surface water absorption, it cannot penetrate deep into the interior to repair microcracks. After long-term immersion in water, moisture will still slowly seep into the aggregate, resulting in a greater strength reduction than the fungal system.
[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing modified and reinforced recycled aggregate, characterized in that, Includes the following steps: S1: Multi-stage crushing and screening of construction waste to obtain continuously graded recycled aggregate; S2: Place the recycled aggregate processed in step S1 into a vacuum impregnation tank, then remove the air from the pores inside the aggregate under vacuum negative pressure, then inject Aspergillus terrestris composite mineralization liquid, and then perform impregnation and coating treatment under normal pressure. After that, take it out, drain it, and perform mineralization curing treatment to obtain pre-mineralized recycled aggregate. S3: Place the pre-mineralized recycled aggregate obtained in step S2 in a sealed carbonization box, heat it to 50~60℃, evacuate it to 10~50kPa and maintain it for 5~30min, then introduce a preheated mixed gas containing CO2 and SO3, and pressurize it to atmospheric pressure within 30~120s to carry out high-concentration pulse infiltration; stop the introduction of SO3, and carry out a diffusion reaction in a CO2 atmosphere. After the reaction is completed, the modified and reinforced recycled aggregate is obtained.
2. The method for preparing modified and reinforced recycled aggregate according to claim 1, characterized in that, In step S1, the construction waste is at least one of waste concrete blocks, brick slag, and waste stone slag; in the continuously graded recycled aggregate, the mass fraction of particles with a diameter of 20~31.5mm is 30%~40%, the mass fraction of particles with a diameter of 10~20mm is 30%~40%, the mass fraction of particles with a diameter of 2.36~10mm is 20%~30%, and the sum of the mass fractions of each particle size component is 100%.
3. The method for preparing modified and reinforced recycled aggregate according to claim 1, characterized in that, In step S2, the Aspergillus terrestris composite mineralization solution includes Aspergillus terrestris mycelium, calcium chloride, and sodium alginate; the molar concentration of calcium chloride in the Aspergillus terrestris composite mineralization solution is 0.5~0.6 mol / L, the mass concentration of sodium alginate is 1~3 g / L, and the mass concentration of Aspergillus terrestris mycelium is 5~8 g / L.
4. The method for preparing modified and reinforced recycled aggregate according to claim 3, characterized in that, The Aspergillus terreus strain is CGMCC 3.10144.
5. The method for preparing modified and reinforced recycled aggregate according to claim 1, characterized in that, In step S2, the vacuum degree of the vacuum negative pressure is -0.09 to -0.095 MPa; the impregnation and coating time is 0.5 to 1.0 h; the temperature during the mineralization curing process is 28 to 32℃, the relative humidity is 85% to 95%, and the time is 16 to 20 h.
6. The method for preparing modified reinforced recycled aggregate according to claim 1, characterized in that, In step S3, the total SO3 injection rate in the high-concentration pulsed infiltration is 1.2% to 1.8% of the dry mass of the recycled aggregate; the diffusion reaction is carried out for 1.5 to 2.0 hours at a CO2 volume concentration of 20% to 25%, a relative humidity of 30% to 55%, and a temperature of 50 to 60°C; the SO3 volume concentration in the mixed gas is 8% to 12%, the CO2 volume concentration is 20% to 30%, and the preheating temperature is 50 to 60°C.
7. The preparation method according to claim 6, characterized in that, The diffusion reaction uses a gradient humidification method to control relative humidity: in the first stage, the relative humidity is 30% to 40% for the first 20 to 30 minutes; in the second stage, the relative humidity is gradually increased to 45% to 55%.
8. A modified reinforced recycled aggregate prepared by the method according to any one of claims 1 to 7.
9. A road base course with high-volume recycled aggregate, characterized in that, The dry material components include the following parts by weight: 70-90 parts of the modified reinforced recycled aggregate as described in claim 8, 3-5 parts of cement, 5-7 parts of slag powder, and 0-20 parts of natural fine aggregate.
10. The method for preparing a road base course with high-volume recycled aggregate as described in claim 9, characterized in that, The process includes the following steps: Weigh the modified and reinforced recycled aggregate, cement, slag powder and natural fine aggregate according to the proportion, dry mix for 2-3 minutes to mix evenly; then add mixing water and wet mix for 3-5 minutes to obtain the base course mixture; spread and compact the mixture to a compaction degree ≥97%, and then cover and water-cur for at least 7 days to obtain the road base course with high-volume recycled aggregate.
Citation Information
Patent Citations
Interface reinforced recycled aggregate, preparation method thereof and recycled aggregate concrete
CN117303774A
Microorganism mineralized recycled coarse aggregate and soil coagulated rock solidified fully-doped recycled aggregate concrete as well as preparation method and application thereof
CN118084377A
Microbial mineralization modified recycled aggregate as well as preparation method and application thereof
CN120192108A